2020
DOI: 10.1021/acs.est.0c05377
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Thin-Film Nanocomposite Membranes with Interlayered Structure: Mechanisms, Recent Developments, and Environmental Applications

Abstract: The separation properties of polyamide reverse osmosis and nanofiltration membranes, widely applied for desalination and water reuse, are constrained by the permeability-selectivity upper bound. Although thin-film nanocomposite (TFN) membranes incorporating nanomaterials exhibit enhanced water permeance, their rejection is only moderately improved or even impaired due to agglomeration of nanomaterials and formation of defects. A novel type of TFN membranes featuring an interlayer of nanomaterials (TFNi) has em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(175 citation statements)
references
References 292 publications
5
161
0
Order By: Relevance
“…Readers are referred to a comprehensive review for the recent progress in the use of sacrificial interlayers in IP. 24 In addition to the use of nanomaterial-tailored supports, another strategy is to perform IP at a free interface between an aqueous phase and an organic phase. 25,26 The liquid interface enables more rapid heat dissipation than that in an aqueous solution trapped in solid support, forming free-standing nanofilms with smooth surfaces due to inhibition of interfacial instability.…”
Section: Constructing Sacrificial Interlayers On the Support Layermentioning
confidence: 99%
“…Readers are referred to a comprehensive review for the recent progress in the use of sacrificial interlayers in IP. 24 In addition to the use of nanomaterial-tailored supports, another strategy is to perform IP at a free interface between an aqueous phase and an organic phase. 25,26 The liquid interface enables more rapid heat dissipation than that in an aqueous solution trapped in solid support, forming free-standing nanofilms with smooth surfaces due to inhibition of interfacial instability.…”
Section: Constructing Sacrificial Interlayers On the Support Layermentioning
confidence: 99%
“…Despite enhanced permeance at 15 L m À2 h À1 bar À1 for the TFN membrane, the specific energy consumption predicted was reduced by a mere 16.6% when compared to commercial TFC membrane with 1 L m À2 h À1 bar À1 permeance. 44 From the marginal reduction in this case, it is evident that energy consumption is more dependent on the osmotic pressure of the feed and the operating conditions rather on permeance. It was observed that energy consumption reduces for operations such as BWRO and NF membranes operating at 5-10 bar pressure.…”
Section: Review Materials Advancesmentioning
confidence: 91%
“…42,43 Last, 2D nanosheets may be applied onto the surface of the membranes to decorate the PA layer in a controlled manner. 44,45 The conventional IP reaction involves removal of the aqueous phase, utilizing rubber roller or airgun or air knife. Emerging innovations open up methods such as vacuum filtration, spin coating and electrospraying-assisted IP reaction techniques which facilitate the contact of the aqueous phase on the support membrane.…”
Section: Interfacially Polymerized 2d-enabled Tfn Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The TFN membranes provided improvement in chlorine resistance and antifouling properties (wang et al, 2011).Despite such unique properties, dispersion of hydrophilic nanoparticles and leaching of nanoparticles into retentate and permeate has raised the environmental concerns and need further research. As the world is facing shortage of freshwater, thin film nanocomposite (TFN) membranes are anticipated to accelerate desalination industry and it can be extended as selective membranes for CO 2 separation (Wong et al, 2016).The incorporation of functionalized fillers such as GO, CNT, TiO 2 , Ag-TiO 2 , MOFs (Figure 10) or organic fillers for specific applications has the potential to enhance membrane performance (Kumar et al, 2020).Recently, an interlayer of nanomaterials (TFNi) membranes showed extraordinary improvement in water flux and selectivity that can be used for the removal of heavy metals and micropollutants at a large scale (Yang et al, 2020).In the near future, high impact TFN membranes with antifouling and biofouling properties, chemical resistance, improved mechanical strength and thermal stability need to be produced by either predisposition of new types of functionalized nanofillers or organic fillers compatible with selective layers of respective membranes. Such design and development of TFN membranes may pave way for more robust membrane systems with increased performance and long term durability providing precise solutions for various commercial water treatment challenges.…”
Section: Future Perspectivementioning
confidence: 99%